Effect of urea and polymer-coated urea on N content of soil and leaves of maize cultivated in Brazilian Cerrado - Kaneko, Flávio Hiroshi; Ferreira, João Paulo; Leal, Aguinaldo José Freitas; van Cleef, Eric Haydt Castello Branco; Galati, Vanessa Cury; Arf, Orivaldo [UNESP] (Elsevier, 2021)
The development of technologies that provide rational and sustainable use of nitrogen fertilizers is among the priorities of agronomic research in 21st century. Therefore, the objective of this study was to evaluate the effects of conventional urea or polymer-coated urea (PCU) on soil mineral nitrogen (N) content, plant dry mass and leaf N content in maize (Zea mays L.), cultivated in two seasons (first and second-crop) and in two regions of the Brazilian Cerrado (Chapadão do Sul - MS and Selvíria - MS). The treatments consisted of the combination of two sources of N (conventional urea or polymer-coated urea) and five doses of N (0, 45, 90, 135 or 180 kg ha−1), in a randomized complete block design, with a 2 × 5 factorial scheme with four replications. The following parameters were evaluated: soil mineral N content (NH4+, NO3- and total mineral N), plant dry mass and leaf N content. Although the PCU did not change the NH4+, NO3- and total mineral N content in the soil, nor the dry mass of the plants, it provided, on average, higher N content in the leaves, when compared to CU. The increasing rates of N linearly increased the levels of NH4+, NO3- and total mineral N content in the soil, as well as the dry mass of the plants and the N content in the leaves, regardless of N source or study location.
Keywords: NH4+; No-till system; NO3-; Policote®; Zea mays L.